Virus-derived peptides for hepatic enzyme delivery - Pratsinis, Anna; Uhl, Philipp; Bolten, Jan Stephan; Hauswirth, Patrick; Schenk, Susanne Heidi; Urban, Stephan; Mier, Walter; Witzigmann, Dominik; Huwyler, Jörg (Molecular pharmaceutics, 2021)
Recently, a lipopeptide derived from the hepatitis B virus (HBV) large surface protein has been developed as an HBV entry inhibitor. This lipopeptide, called MyrcludexB (MyrB), selectively binds to the sodium taurocholate cotransporting polypeptide (NTCP) on the basolateral membrane of hepatocytes. Here, the feasibility of coupling therapeutic enzymes to MyrB was investigated for the development of enzyme delivery strategies. Hepatotropic targeting shall enable enzyme prodrug therapies and detoxification procedures. Here, horseradish peroxidase (HRP) was conjugated to MyrB via maleimide chemistry, and coupling was validated by SDS-PAGE and reversed-phase HPLC. The specificity of the target recognition of HRP-MyrB could be shown in an NTCP-overexpressing liver parenchymal cell line, as demonstrated by competitive inhibition with an excess of free MyrB and displayed a strong linear dependency on the applied HRP-MyrB concentration. In vivo studies in zebrafish embryos revealed a dominating interaction of HRP-MyrB with scavenger endothelial cells vs xenografted NTCP expressing mammalian cells. In mice, radiolabeled 125I-HRP-MyrBy, as well as the non-NTCP targeted control HRP-peptide-construct (125I-HRP-alaMyrBy) demonstrated a strong liver accumulation confirming the nonspecific interaction with scavenger cells. Still, MyrB conjugation to HRP resulted in an increased and NTCP-mediated hepatotropism, as revealed by competitive inhibition. In conclusion, the model enzyme HRP was successfully conjugated to MyrB to achieve NTCP-specific targeting in vitro with the potential for ex vivo diagnostic applications. In vivo, target specificity was reduced by non-NTCP-mediated interactions. Nonetheless, tissue distribution experiments in zebrafish embryos provide mechanistic insight into underlying scavenging processes indicating partial involvement of stabilin receptors.
Gesehen am 21.06.2021